Asssociation of vitamin D with autoimmune ophthalmopathy in Graves’ disease (Ukrainian Journal of Ophthalmology, 2025)
Background: The role of vitamin D in the development of autoimmune thyroid diseases has been actively discussed in the recent literature. Numerous studies have demonstrated an association of low vitamin D levels with autoimmune thyroiditis, with correlations with antithyroid antibody levels, thyroid hormone levels, disease severity and thyroid gland volume, both in adults and in children. However, there are a few relevant reports on Graves’ disease (GD), and only one relevant report is available on GD associated with autoimmune ophthalmopathy (AO). Given that GD complicated by AO is a classic autoimmune disease, it will be interesting to investigate the role of vitamin D in its pathogenesis.Purpose: To examine vitamin D levels and to determine correlations between this characteristic and thyroid-stimulating hormone receptor antibodies (TSH-R-Ab) in patients with Graves’ disease complicated by immune ophthalmopathy.Material and Methods: Serum levels of 25(OH)D, TSH, TSH-R-Ab and parathyroidal hormone (PTH) were measured in 131 patients with GD. Study patients were divided into two groups based on the presence or absence of ophthalmopathy. Group 1 comprised 81 GD patients with AO, and group 2 comprised 50 GD patients without AO. Clinical severity of AO was classified using the NOSPECS. Thirty-two, 30 and 19 patients had class 2b, class 3a or 3b, and class 4a, respectively. Variation statistics with Student t test was used for statistical analyses. The level of significance p ? 0.05 was assumed. Data are presented as mean ± standard error of mean. Pearson correlation analysis was used to identify possible correlations between variables.Results: All patients were euthyroid, and the mean TSH level in group 1 was 1.33±0.35 mU/L, and in group 2, 0.5 ± 0.2 mU/L (Р > 0.05). TSH-R-Ab levels were higher than normal in both groups of patients (group 1: range, 0.8 U/L to 21 U/L , mean value, 14.05± 2.7 U/L ; group 2: range, 1.8 U/L to 14.3 U/L , mean value, 31.0 ± 2.22 U/L; the difference between groups was not significant, р > 0.05). This was anticipated since these abnormalities are pathogenetic in GD. Serum levels of 25(OH)D in both groups were lower than normal (42.98 ± 2.82 nmol/L in group 1 vs 58.12 ± 4.2 nmol/L in group 2; р 0.05). TSH-R-Ab levels were negatively linearly correlated with the serum 25(OH)D level in the study cohort (elevated TSH-R-Ab levels correlated with low 25(OH)D levels).Conclusion: First, there was no statistically significant difference in TSH-R-Ab levels between Graves’ disease patients with AO and those without AO (14.05±2.7 U/L and 31±2.22 U/L, respectively; р > 0.05). Second, the mean serum 25(OH)D level for the study cohort of Graves’ disease patients (47.63 ± 2.48 nmol/L) was insufficient, and the mean level for patients with AO was significantly lower than the mean level for patients without AO (42.98 ± 2.82 nmol/L vs 58.12 ± 4.2 nmol/L; р
Keywords: autoimmune ophthalmopathy; Graves’ disease; vitamin D